Cover Feature: Tuning the Optical Properties of Phenanthriplatin: Towards New Photoactivatable Analogues (ChemPhotoChem 11/2017). Issue 11 (30th October 2017) - Cerón‐Carrasco, José Pedro; Jacquemin, Denis
Abstract : The Cover Feature illustrates how an all‐atomistic chemical model can be used to rationalise the photoactivation of novel monovalent metallodrugs based on the parent phenanthriplatin structure. More information can be found in the Article by J. P. Cerón Carrasco et al. onpage 504 in Issue 11, 2017 (DOI:10.1002/cptc.201700090 ).